2022
DOI: 10.1371/journal.pone.0266698
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic factors influence on an omnivore’s gut microbiome

Abstract: Gut microbiomes (GMBs), complex communities of microorganisms inhabiting the gastrointestinal tracts of their hosts, perform countless micro-ecosystem services such as facilitating energy uptake and modulating immune responses. While scientists increasingly recognize the role GMBs play in host health, the role of GMBs in wildlife ecology and conservation has yet to be realized fully. Here, we use brown bears (Ursus arctos) as an ecological model to (1) characterize GMB community composition associated with loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Given the high level of among-individual variation detected in the bacterial communities of marten in this study, as well as the findings from other studies of carnivore gut microbiomes (e.g., mink [ 84 ], Ursus spp. [ 41 , 85 ]), it is not surprising that we detected statistically significant differences in unweighted UniFrac between live-trapped and harvested marten. As a metric, unweighted UniFriac disproportionately weights taxa that are present at low relative abundances.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Given the high level of among-individual variation detected in the bacterial communities of marten in this study, as well as the findings from other studies of carnivore gut microbiomes (e.g., mink [ 84 ], Ursus spp. [ 41 , 85 ]), it is not surprising that we detected statistically significant differences in unweighted UniFrac between live-trapped and harvested marten. As a metric, unweighted UniFriac disproportionately weights taxa that are present at low relative abundances.…”
Section: Discussionmentioning
confidence: 79%
“…PLOS ONE (e.g., mink [84], Ursus spp. [41,85]), it is not surprising that we detected statistically significant differences in unweighted UniFrac between live-trapped and harvested marten. As a metric, unweighted UniFriac disproportionately weights taxa that are present at low relative abundances.…”
Section: Plos Onementioning
confidence: 76%
See 1 more Smart Citation
“…In congruence with the NVH, brown bears exhibit the ability to achieve similar body conditions across substantial range of among-individual dietary niche variation [7][8][9] . In a previous study, we characterized brown bear GMB bacterial community composition associated with location, season, and reproductive condition with taxa relative abundance 44 . We found that brown bear GMBs vary in membership and overall composition, complementary to the nutritional landscape of each location and that GMB composition presents similarly high levels of among-individual variation as diet.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the gut microbiome in wildlife elicits particular challenges. Interindividual variation may mask the effects of geographic location, diet, reproductive groups [91], or body condition [92], making it difficult to identify what constitutes a "typical" or core microbiome for a given host species, much less to detect statistically significant differences among populations [93]. Limited populations and low sample sizes inherent to endangered and elusive species further compound these issues.…”
Section: Common Pitfalls Within Rhinoceros Gut Microbiome Studiesmentioning
confidence: 99%